Changes in levels of actin and tubulin mRNAs upon the lectin activation of lymphocytes. - McCairns, E (1984)
The expression of beta-actin, gamma-actin, alpha-tubulin, and beta-tubulin mRNA during the lectin activation of human peripheral blood lymphocytes was examined with specific cDNA clones. The resting lymphocyte has a low level of both alpha- and beta-tubulin mRNAs, and these increase 10-fold after 72 h of lectin stimulation in which maximum cell transformation is achieved. Although there is a slight increase in tubulin mRNA during the first 6 h, most of the increase occurs between 6 and 24 h as the cells start to increase their RNA content and progress from G0 into G1. Both beta- and gamma-actin mRNAs are more abundant than the tubulin mRNAs in resting cells, with beta-actin mRNA being the major species. Upon activation, beta-actin mRNA increases threefold, whereas gamma-actin mRNA increases almost sixfold. Both beta- and gamma-actin mRNA are elevated 2.5-fold as early as 6 h, the gamma-actin mRNA level then increasing more than beta-actin between 6 and 24 h, resulting in the reduced beta-actin/gamma-actin mRNA ratio. The lectin-stimulated lymphocyte has a similar beta-actin/gamma-actin mRNA ratio as that of the human leukemic T-lymphoblast cell line CCRF-CEM. These increases are over and above the general increase in polyadenylated RNA content upon lectin activation. On returning to a noncycling state, the levels of these cytoskeletal mRNAs decrease. There were two beta-tubulin mRNAs present in lymphocyte cytoplasm, one of 1.8 kilobases and one of 2.8 kilobases in length. The nongrowing lymphocytes had relatively lower levels of the larger sized mRNA. Upon stimulation, the relative level of the larger mRNA was increased, and at 72 h the cells had approximately equal levels of both mRNAs as did the leukemic lymphoblasts.